Study Of Cows Of The Golshtin Breed By Comparing Generally Known Indicators During The Second Lactation - daughter, Mirsaidova Zukhra Shukhrat; Nayimovich, Khujamov Zhurabek (Journal of Medical Genetics and Clinical Biology, 2024)
This article examines and compares the milk production of Holstein cows from Dutch, German, and Danish selection based on their constitution. The study focuses on milk yield, milk fat, milk protein yield, and 4% milk yield per 100 kg of live weight. Data was provided.